A semi-definitive list of worst nightmares - Sutherland, Krystal (G.P. Putnam's Sons, 2017)
"Esther Solar is determined to break a curse that has doomed her entire family to debilitating phobias, only to encounter a new fear she hadn't counted on: first love"--